Design of a wireless network for renewable energy sources using wi-fi - See Toh, Lai Bun. (2011)
Energy industry observers have considered renewable energy as an alternative and practical source of energy generation. It is predicted that the world will undergo a major transition in energy sources over the next few decades and clearly, renewable energy will be a popular choice. This project is to design an intelligent wireless network for monitoring these energy sources in the Microgrid and record the energy source profile as database. Collection of energy source profile will be transmitted using Wi-Fi. Performance of using Wi-Fi will be studied.Renewable Energy sources are widely used in many countries. It can help reduce the usage of Earth‟s depleting natural resources and also reduce the emission of harmful chemicals and gases that will be devastating to humans. Hence, developing a convenient and cost efficient monitoring system is very crucial to ensure smooth operation of the renewable energy sources and also promote the use of renewable energy.